Prenatal diagnosis of congenital anomalies ultrasound. - Pinedo, José (2015)
One thousand thirty three ultrasound studies performed after the second trimester in 900 pregnant women at a first hospital level ultrasound screening unit were correlated with findings in the newborn babies. Twenty nine newborns presented congenital anomalies with an incidence of 3,17%. First level ultrasound screening detection rate was 50% with 99% specificity, 40% false positives and 2% false negatives. With respect to major congenial anomalies, corresponding rates were 63%, 99%, 40% and 1%. First level ultrasound screening has an acceptable detection rate and excellent specificity for congenital anomalies identification and should be a useful diagnostic procedure in low prevalence populations.